AN ECONOMIC AND ECOLOGICAL VALUATION OF MANGROVE ECOTOURISM USING A CHOICE MODELLING APPROACH TO ASSESS COMMUNITY PREFERENCES IN EAST KALIMANTAN - Rosid, Tamam (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
The objective of this study is to estimate the community’s willingness to pay (WTP) and to identify the factors that influence their preferences in efforts to improve the environmental quality of mangrove ecotourism areas in East Kalimantan. This research employs the choice modelling method to explore public preferences regarding the attributes of mangrove ecosystems that hold both economic and ecological value. The sample was obtained using a random sampling method, specifically by randomly selecting visitors to the mangrove ecotourism area. Data analysis was carried out using a choice modelling approach, particularly employing binary logistic regression to examine the influence of various attributes on respondents’ choices. The results indicate that the average WTP for improving the environmental quality of mangrove areas is IDR 7,500. Moreover, community preferences in supporting environmental improvements are significantly influenced by several factors, including travel costs to the location, the current condition of the mangrove forest ecosystem, respondents’ education levels, and the ecological and social attributes of the mangrove ecotourism site.